Pajanan Pestisida Sebagai Faktor Risiko Hipotiroidisme pada Wanita Usia Subur di Daerah Pertanian - Suhartono Suhartono; RRJ. Sri Djokomoeljanto; Suharyo Hadisaputro; Hertanto Wahyu Subagio; Apoina Kartini; Suratman Suratman (MEDIA MEDIKA INDONESIANA, 2012)
Pesticide exposure as a risk factor for hypothyroidism in women at childbearing age in agricultural areasBackground: Hypothyroidism in women at childbearing age (WCA) will cause reproduction disorder, i.e. infertility, spontaneous abortion, impaired growth and development of foetus, placental abruption, and preterm delivery. Pesticide exposure is suspected to cause hypothyroidism. The research objective is to prove that pesticide exposure is a risk factor for hypothyroidism among WCA in agricultural areas.Methods: Case-control studies were used as study designs. Study subjects were 44 WCA as cases and 45 WCA as controls. Pesticide exposure was measured by asking WCA’s involvement in agricultural activities using structured questionnaire and by checking their levels of cholinesterase. Hypothyroidism was determined based on the results of TSH, FT4, and T3 level. Confounding variables were also measured. These variables were age, body mass index (BMI), participation in hormonal contraception, liver function, urinaryiodine excretion, urinary thiocyanate level and blood lead level. Chi-square test, OR (95% CI), and multivariate logistic regression were implemented to test the hypothesis.Results: Pesticides exposure is a risk factor for hypothyroidism (crude-OR=3.04; 95% CI=1.20-7.81; nilai p=0.033 and adjusted OR=3.31, 95% CI=1.25 to 8.78, p=0.016). The higher the degree of exposure, the greater the risk of having hypothyroidism.Conclusion: Pesticides exposure is a risk factor for hypothyroidism among WCA in agricultural areas.Keywords: Pesticide exposure, risk factor, hypothyroidism, women at childbearing age, agricultural areaABSTRAKLatar belakang: Hipotiroidisme pada kelompok wanita usia subur (WUS) dapat menyebabkan gangguan reproduksi, seperti infertilitas, abortus spontan, gangguan tumbuh-kembang janin, dan kelahiran prematur. Pajanan pestisida dapat mengganggu fungsi tiroid. Tujuan penelitian adalah membuktikan bahwa pajanan pestisida merupakan faktor risiko hipotiroidisme pada WUS di daerah pertanian.Metode: Desain penelitian yang digunakan adalah kasus-kontrol. Subyek penelitian adalah 44 WUS sebagai kasus dan 45 sebagai kontrol. Pajanan pestisida diukur menggunakan kuesioner dan pemeriksaan kadar kolinesterase. Kejadian hipotiroidisme diukur menggunakan parameter kadar TSH, FT4 dan T3. Variabel perancu yang diukur meliputi umur, indeks massa tubuh (IMT), penggunaan KB hormonal, fungsi hati, ekskresi yodium urin, kadar tiosianat urin, dan kadar Pb darah. Uji hipotesis yang digunakanadalah uji Chi-square, uji OR (95%CI), dan regresi logistik multivariat.Hasil: Pajanan pestisida merupakan faktor risiko hipotiroidisme pada WUS di daerah pertanian (crude-OR=3,04; 95%CI=1,20- 7,81; nilai p=0,033 dan adjusted OR=3,31; 95%CI=1,25-8,78; p=0,016). Semakin tinggi derajat pajanan pestisida, semakin besar risiko terjadinya hipotiroidisme.Simpulan: Pajanan pestisida merupakan faktor risiko kejadian hipotiroidisme pada WUS di daerah pertanian.